Replication Studies on Significant Differences in Personality Profiles of Securely and Insecurely Attached Psychotherapists and Dentists - Peter, Burkhard; Wolf, Thomas G. (Frontiers in Psychology, 2021)
This study contributes to the therapist variable in general and the personality profile of securely and insecurely attached psychotherapists and other health care professionals in particular. In a preceding study, Peter and Böbel (2020b) found that insecurely attached psychotherapists differ in 9 personality styles from securely attached ones. The aim of the present study was to replicate these findings and to investigate whether they also apply to other health professions such as dentists. 891 subjects from two German professional societies for hypnosis were surveyed online with a personality questionnaire (PSDI) and an attachment questionnaire (RSQ). Since these subjects were interested in hypnosis and used it in their practice (HYP), 150 dentists without a hypnosis context (NONHYP) were studied as a control group with the same survey. The results of the preceding attachment study could be replicated: Insecurely attached health care professionals differed significantly from securely attached ones in the same nine (plus one, i.e. ten) personality styles if they use psychological methods including hypnosis. If they don´t use psychological methods (like the NONHYP dentists), they differ in half of the personality styles. No within-sample and no between-sample differences have been found in the assertive/antisocial (AS) personality style. No within-sample differences have also been found in the conscientious/compulsive (ZW) and in the intuitive/schizotypal (ST) personality style. However, large between-sample differences were obvious in ZW and the ST. Both of the dentist´s samples were much more compulsive than the two psychotherapeutic samples. And, both of the HYP samples were much more schizotypal than the NONHYP samples. The latter is the general signature of those individuals who are interested in hypnosis and were metaphorically termed homo hypnoticus by Peter and Böbel (2020a). It seems that AS, ZW and ST are independent of attachment.